Landscape planning of the city of Cuiabá - MT: Case study of urbanized green areas in the Westside - Benini, Sandra Medina (National Journal of City Management, 2020)
This research aimed to carry out an analysis of the quality of Urbanized Green Public Areas (AVPUs), such as squares, gardens and urban parks, which are intended for leisure and recreation in the contemporary city. As the focus of the study, the west area of the city of Cuiabá-MT was chosen. For the development of this qualitative research, methodological procedures were adopted that were based on a logical investigation, divided into three phases: open or exploratory, data collection and analysis and systematic interpretation of data. As a result, it was found that there is a lack not only in the amount of public spaces intended for leisure and recreation, as well as the quality of AVPUs that were found, which shows the absence of public policies aimed at the population.